2009
DOI: 10.1111/j.1467-954x.2009.01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Activity, Social Isolation and Ethnicity

Abstract: This paper explores the extent to which social activity in England and Wales varies by ethnic group and whether risks of social isolation are higher for some groups than others. It aims to enhance our understanding of social deprivation as a particular dimension of poverty and its variation by ethnicity.It also provides empirical evidence that informs discussions of social capital formation which focus on informal measures of participation, and amplifies our understanding of ethnic capital within groups. Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…Older Malays were less likely to be at risk of social isolation than other ethnic groups such as Chinese and Indians. This finding supports the results from previous studies . It has been suggested that ethnicity may moderate the relationship between sociodemographic factors and social isolation …”
Section: Discussionsupporting
confidence: 92%
“…Older Malays were less likely to be at risk of social isolation than other ethnic groups such as Chinese and Indians. This finding supports the results from previous studies . It has been suggested that ethnicity may moderate the relationship between sociodemographic factors and social isolation …”
Section: Discussionsupporting
confidence: 92%
“…At the individual level, certain personal characteristics and life-course transitions have been associated with a higher risk of social isolation. The former includes: being 75 years and over [11], living or spending a significant amount of time alone [11], having limited financial resources [12], having psychological vulnerabilities such as a learning disability [13], belonging to certain minority groups [14], language barriers [15,16], and having no children [1,16]. Life-course transitions associated with social isolation include: a decline in general health including poor vision or loss of hearing [11,12], physical disability or loss of mobility [12], receiving a diagnosis of dementia [17], retirement [18], loss of income [12], losing the ability to drive [19], moving to a care home [12,18], losing a partner [18], becoming a caregiver [18], and having children leave home especially if they move a long distance away [11].…”
Section: Risk Factors For Social Isolationmentioning
confidence: 99%
“…The Count Me In Census of inpatients in mental health units in 2009(Care Quality Commission & National Mental Health Development Unit, 2010, estimated that the age-and sex-standardised rates for admission for Pakistani women (2009, standardised ratio [SR] = 65, confidence interval [CI] = 53-79; 2010, SR = 70, CI = 57-84) were less than for white British women (2009, SR = 94, CI = 93-96; 2010, SR = 95, CI = 93-96) and less than the average rates (100) for women. However, the results from the years 2005 to 2008 suggested that the rates of admission for Pakistani women were no different from the average.…”
Section: Inpatient Servicesmentioning
confidence: 99%